Penerapan Pencatatan Laporan Keuangan Berdasarkan SAK-EMKM pada UMKM - Muammar Khaddafi; Ade Andriana Salsabila; Annisa Sagala; Ajeng Retno Anggraini; Icha Riani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important contribution in supporting the national economy, especially in terms of job creation and strengthening the local economy. However, most MSMEs still face challenges in compiling financial statements that are in accordance with applicable accounting standards. This study aims to analyze the extent to which the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) has been implemented by MSME actors, as well as identify the obstacles faced in the process. The research approach used is qualitative descriptive, with data collection techniques through interviews, direct observation, and document review. The findings of the study show that the level of understanding of MSME actors towards SAK-EMKM is still low, and the implementation of these standards is not evenly distributed. The main causative factors include limited accounting knowledge, lack of professional assistance, and lack of access to technical training. In addition, most MSMEs still rely on manual recording without referring to correct accounting principles, making it difficult in the audit process or applying for loans to financial institutions. Another obstacle is the lack of digital literacy in financial management, as well as the assumption that the preparation of financial statements is not a top priority. In fact, well-structured financial statements can be an important tool in business decision-making and open access to funding. This study recommends the importance of collaboration between the government, academics, and financial institutions to provide training, mentoring, and a simple reporting system that is in accordance with the characteristics of MSMEs. This effort is expected to increase the awareness and ability of MSMEs to manage finances in an accountable and transparent manner, as well as support business growth and sustainability in the long term.